Embryonic Neural Stem Cell Differentiation to Aldynoglia Induced by Olfactory Bulb Ensheathing Cell-Conditioned Medium - Ortuño-Sahagún, Daniel; Rojas-Mayorquín, Argelia E.; Camins, Antoni; Pallàs, Mercè (IntechOpen, 2011)
None